Methods Of Determining DSN MUI Fatwa On Sharia Economics - Riskyka, Riskyka; Winda Pricilia; Dwi Cahyani; Muhammad Nur Iqbal (Fox Justi : Jurnal Ilmu Hukum, 2025)
The National Sharia Council of the Indonesian Ulema Council (DSN-MUI) in determine the related fatwa sharia economy . The fatwa issued by DSN-MUI holds role important in determine guidelines as well as appropriate policy​ with sharia principles in practice economy in Indonesia. Research This use approach qualitative descriptive with focus on studies case in the process of determination several DSN-MUI fatwas regarding Islamic economics . Data obtained through interview with DSN-MUI member , analysis fatwa documents , as well as study relevant literature . Research results show that determination of the fatwa by DSN-MUI through a number of stages , namely collection information , discussion scientific , study library , consultation with experts , and finally reach consensus For produce a fatwa. This process aiming For ensure the fatwa is issued No only in accordance with sharia rules , but can also follow development dynamic economy . In addition , research This disclose that DSN-MUI uses a collective ijtihad approach that involves various parties , including academics , practitioners , and regulators, in order to ensure validity as well as wide acceptance​ against the fatwa issued . Findings from study This give contribution significant in development sharia economy in Indonesia and can become reference in the issuance of a similar fatwa in a country with system Islamic economics .